The Effects of Home-Based Cognitive Training on Verbal Working Memory and Language Comprehension in Older Adulthood - Payne, Brennan R.; Stine-Morrow, Elizabeth A. L. (Frontiers in Aging Neuroscience, 2017)
Effective language understanding is crucial to maintaining cognitive abilities and learning new information through adulthood. However, age-related declines in working memory (WM) have a robust negative influence on multiple aspects of language comprehension and use, potentially limiting communicative competence. In the current study (N = 41), we examined the effects of a novel home-based computerized cognitive training program targeting verbal working memory on changes in verbal working memory and language comprehension in healthy older adults relative to an active component-control group. Participants in the WM training group showed non-linear improvements in performance on trained verbal working memory tasks. Relative to the active control group, WM training participants also showed improvements on untrained verbal working memory tasks and selective improvements across untrained dimensions of language, including sentence memory, verbal fluency, and comprehension of syntactically ambiguous sentences. Though the current study is preliminary in nature, it does provide initial promising evidence that working memory training may influence components of language comprehension in adulthood and suggests that home-based training of working memory may be a viable option for probing the scope and limits of cognitive plasticity in older adults.